Development, try-out and evaluation of enrichment activities on the extraction of oil from flowers - Sabando, Emelinda P. (1985)
The focus of this study is on the instructional materials that would develop skills in gardening among the educable mentally retarded in the intermediate level on the assumption that given proper training and guidance, the educable mentally retarded can learn simple crop cultivation technology.